PERKEMBANGAN ALAT BUKTI DALAM PEMBUKTIAN TINDAK PIDANA BERDASARKAN UNDANG UNDANG KHUSUS DAN IMPLIKASI YURIDIS TERHADAP KUHAP - Alcadini Wijayanti, Pujiyono, Bambang Dwi Baskoro (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Along with the rapid advancement of such crimes are characterized by transnational crime, extraordinarycrime to transborderless crime and the birth of a new modus operandi of the crime, the effects caused by the greater evil. To law enforcement for crimes that are very advanced, the legal arrangements in Indonesian legislation, namely the Code of Penal Code (Code), which is a translation of the Wetboek Van Voor Strafrecht Netherlands Indies and policies in Indonesia would have a very inadequate Methods of research in legal writing is analytical description, which describes the applicable legislation related to legal theories and practices related to the implementation of positive law above problems. This type of research in writing this law using normative research, sources of data in this study is a secondary data source. Data collection methods used in the writing of this law is the study of literature, while the data analysis method used is descriptive qualitative The setting and the development of evidence proving a crime in criminal law legislation in Indonesia has experienced the development of science and technology, crime and modus operandi, and people will always influence the development of the evidence in the criminal procedure law in Indonesia, which is set in Criminal Procedure Code or in special legislation. Which will be discussed in the writing of this law is the Law of the Republic of Indonesia Number 31 Year 1999 on Eradication of Corruption, as amended by Law of the Republic of Indonesia Number 20 of 2001 and Law of the Republic of Indonesia Number 11 Year 2008 on Information and Electronic Transaction